THE IMPACT OF THE CROSS-BORDER CULTURAL PHENOMENON OF THE KOREAN WAVE ON CULTURAL TRANSFORMATION IN SAUDI ARABIA - Abdullah Abdullah; Ismail Ubaidillah (Arabic Literature Department, 2023)
Globalization’s impact on culture is vividly apparent in the infiltration of foreign cultures into different countries, as exemplified by the permeation of the Korean Wave, or “Hallyu,” in Saudi Arabia. Among the Saudi youth, Korean TV dramas (K-dramas) and Korean Pop Music (K-POP) have experienced immense popularity, marking a significant shift in traditional ideological, political, and economic boundaries. This cultural shift facilitates an enhanced exchange between Korea and Saudi Arabia, igniting a newfound interest in the Korean language and culture. Concurrently, Korean fashion and beauty trends have seized the attention of Saudi Arabian youth, influencing their clothing, hairstyling, and beauty routines. This research aims to unravel the extent of influence and transformation instigated by such transnational cultural phenomena on local cultures. Utilizing a qualitative approach, this study conducts a literature review to explore the depth and breadth of the Korean Wave’s impact on Saudi Arabian society. Researchers face particular challenges, including limited research availability, language and cultural context, and the reliability of available data. However, despite these constraints, the study provides valuable insights into cultural globalization, media influence, and the dynamics of cross-cultural interactions, advancing our understanding of this evolving global landscape.